Analysis of electrochemical performance of lithium carbon fluorides primary batteries after storage - Liu, Wen; Yan, Tingfang; Guo, Rui; Dang, Guoju; Li, Yong; Pei, Haijuan; Yan, Qibin; Xie, Jingying (Journal of Materiomics, 2021)
Lithium carbon fluorides (Li/CFx) primary batteries are of highly interests due to their high specific energy and power densities. The shelf life is one of the major concerns when they are used as backup power, emergency power and storage power in landers, manned spacecraft or military applications. In this work, real-time storage tests are carried out for both energy-type and power-type Li/CFx pouch batteries at 25 °C. Accelerated storage tests are performed at elevated temperature of 55 °C. The electrochemical tests are conducted throughout the aging period of 0–365 days for various batteries to study the effects of temperature on both type of batteries. The observed electrochemical behaviors are explained with the evidences from multiple characterizations for post-tested samples. [Display omitted] •CFx materials determine the electrochemical performance.•Storage at 55 °C affects the delivered specific capacity and discharge voltage.•The formation of LiF results in the capacity fading.•The increasing film impedance leads to the drop of discharge voltage.